Evaluation of yellow corn (Zea mays L.) varieties for tolerance to stunting. - Ortíz, José (2016)
Eight yellow corn cultivars from the "Proyecto de Achaparramiento de maiz" (Corn Stunting Project) were evaluated under five environments in Central America and the Caribbean. The specific objectives were to evaluate the degree of tolerance to the stunting, to quantify the progress achieved through selection and to detect the most promissing yellow population. The 'CESDA-88' was the variety showing the lowest stunting percentage (15.6%) and a good yield. Profits due to selection were produced by the population 36, in one locality only. The regression analysis showed that the yield was not significatively affected by the stunting percentage. Because of these results, our Project has decided to increase its efforts on the population CESDA-88.